Bioinformatic approach to predict structure, sequence motif and expression level of breast cancer biomarker molecule: protein and miRNA - Ferdous, Jannatul (BRAC University, 2016)
A Dissertation Submitted in Partial Fulfillment of the Requirements’ for the Degree of Bachelor of Science in Biotechnology.